Carry Trade vs. Deposit-Driven Euroization - Geng, Nan (IMF Working Papers; Working Paper ;, 2018)
Financial 'euroization'-or 'dollarization' outside of Central and Eastern Europe-is typically analyzed as a singular phenomenon that can be traced to a common set of factors. This paper argues that two types of euroization need to be distinguished, which have different causes, economic consequences, and policy implications: carry trade euroization that emerges when households and corporations seek to exploit interest rate differentials between foreign currency loans and local currency deposits, and deposit-driven euroization that is rooted in distrust in the local currency as a savings vehicle. We present a theoretical framework that sketches key features of both euroization types, and test it with data from 28 Emerging European and Central Asian economies.